MAKNA MANUHIR DALAM KEHIDUPAN MASYARAKAT DAYAK NGAJU DI KOTA PALANGKA RAYA - Natalia, Desi; Tarantang, Jefry; Astiti, Ni Nyoman Adi (IAIN Palangka Raya, 2020)
It was known that Dayak people as well as other tribes had its own norms and laws,